Baja Tulangan pada Bangunan Gedung - Dharma, Budhi (Universitas Diponegoro, 2006)
Abstract In a building structure, concrete need addition capable to arrest, detain attractive force to arise in the system that is bone steel. Bone steel can in the form of weaved steel strand of metal network or bar and cross of matting, and use by plate construction, other structure and listplank, Interesting strand of metal minimum ultimit become militant 170 = 1700 Mpa, and strand 180= 1800 Mpa. Nature of physical become militant bone that is tension melt, and elastic modulus, can be seen by tension diagram and steel bone bar strain, and specification for iron used by standard of JIS nad PBI 197l. For the iron of artless iron and also thread of quality determined by nature of ats chemical formation and physical installation of bone have to fulfill economic and technical requipment, because concrete iron reprsent costly shares at reinforce concrete system. Extention out down by place which shouldering smallest momen effect of encumbering, by tacking on gasses and mechanic. Depository of bone steel conducted in such a manner to be able to prevent distortion, corrosion, damage and contamination. Key word : bone steel.